Особливості перебігу хірургічної менопаузи у жінок репродуктивного та перименопаузного віку на тлі патології щитоподібної залози - Хабрат, Б. В.; Яроцький, М. Є.; Литвак, О. О.; Лисенко, Б. М.; Коноваленко, В. І.; Дашук, Т. І. (Clinical Endocrinology and Endocrine Surgery, 2010)
Results of complex investigation and treatment of 100 women have shown that syndrome of surgical menopause at thyroid dysfunction has been developed from first days of post operative period in 100% cases and has more severe clinical course that manifestated with increase in folliclestimulating hormone, luteinizing hormone and prolactin, decrease in estradiol and progesterone and also decrease in thyrothropin (TSH) and thyroid hormones in women with hypothyroidism vice versa, increase in thyrothropin (TSH) and Т4, Т3 in women with hyperthyroidism during 6 months. Use of substitutive hormonal therapy from first days of postoperative period allows to prevent development of syndrome of surgical menopause in women with thyroid pathology and progression of thyroid dysfunction that proove presence of connection between reproductive and thyroid function.